2021
DOI: 10.1029/2021gl096403
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Dissipation at Kinetic Scales in the Turbulent Reconnection Outflow

Abstract: Magnetic reconnection is a very important physical process that converts magnetic energy into particle energy accompanied by the change of magnetic field topology, which is responsible for many explosive phenomena in space, astrophysical, and laboratory plasmas (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 43 publications
7
44
0
Order By: Relevance
“…In contrast, the electrons' energization occurred at a local region. The small and patchy regions with strong current density (>1.0 J rms ) provided rapid energization to electrons, consistent with a recent study, where electron heating occurred in the regions with the strong current density (Huang et al 2022). The difference between ions and electrons may be supported by the electron-only reconnection, which always occurs with strong current density (Phan et al 2018;Stawarz et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, the electrons' energization occurred at a local region. The small and patchy regions with strong current density (>1.0 J rms ) provided rapid energization to electrons, consistent with a recent study, where electron heating occurred in the regions with the strong current density (Huang et al 2022). The difference between ions and electrons may be supported by the electron-only reconnection, which always occurs with strong current density (Phan et al 2018;Stawarz et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…At the same time, it is shown that the setting of adequate boundary conditions on the sphere around the Sun, taken with the same order of SW parameters from experimental observations, gives the underestimated temperature of SW plasma at low latitudes and does not explain the features of radial plasma temperature profiles in the subequatorial region. This suggests the necessity to take into account some additional heating factors in the model, both global (e.g., processes in the solar corona) and local (e.g., turbulence [87], shock waves [88], and magnetic reconnection in SW [13]).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic reconnection is a fundamental process of transferring energy between the plasmas and the fields. It is often the case to observe the reconnection in the interplanetary space and geo‐space environment, such as magnetopause (e.g., Burch, Moore, et al., 2016; Burch, Torbert, et al., 2016; Huang et al., 2021; Zhong et al., 2020), magnetosheath (e.g., Phan et al., 2018; Retino et al., 2007), foreshock (e.g., Jiang et al., 2021), and magnetotail (e.g., Huang et al., 2010, 2012, 2016, 2017, 2018, 2022; Jiang et al., 2019; Torbet et al., 2018; Zhou, Deng, et al., 2019; Zhou, Huang, et al., 2019; Zhou et al., 2021). The crucial region of reconnection is distinguished by the ion diffusion region (IDR) and electron diffusion region (EDR).…”
Section: Introductionmentioning
confidence: 99%
“…), is defined by two parts, the inner EDR and the outer EDR (e.g., Hwang et al., 2017; Karimabadi et al., 2007; Xiong et al., 2022; Zenitani et al., 2011). The width of the inner EDR along outflow direction is measured at several ion inertial lengths (E+ve×B0 $E+{v}_{e}\times B\ne 0$) and signified with positive energy conversion di ${d}_{i}$ (e.g., Burch, Moore, et al., 2016; Burch, Torbert, et al., 2016; Huang et al., 2018; 2019, 2022, Zhou, Deng, et al., 2019; Zhou, Huang, et al., 2019). The positive conversion means that the energy is converted from the magnetic field to the particles in the inner EDR, thus resulting in the particles' heating as well as acceleration.…”
Section: Introductionmentioning
confidence: 99%